An External Coincidence Model for the Lunar Cycle Reveals Circadian Phase-Dependent Moonlight Effects on Coral Spawning. Issue 2 (April 2023) - Komoto, Hideyuki; Lin, Che-Hung; Nozawa, Yoko; Satake, Akiko
Many marine organisms synchronously spawn at specific times to ensure the success of external fertilization in the ocean. Corals are famous examples of synchronized spawning at specific lunar phases, and two distinct spawning patterns have been observed in two dominant taxa: merulinid corals spawn at regular lunar phases, several days after the full moon, whereas Acropora corals spawn at more irregular lunar phases around the full moon. Although it has been suggested that the two coral taxa have different responses to moonlight and seawater temperature, their spawning times have never been analyzed by integrating the two environmental factors, resulting in an incomplete understanding of the regulatory mechanisms of spawning. In this study, we developed a new predictive model of coral spawning days by integrating moonlight and temperature effects based on the external coincidence model for the lunar cycle. We performed model fitting using a 10-year monitoring record of coral spawning time in Taiwan. Our model successfully demonstrated the synergistic effects of moonlight and temperature on coral spawning time (days) and provided two testable hypotheses to explain the different spawning patterns regarding the preparation (maturation) process for spawning and the sensitivity to moonlight at different circadian phases: (1) Acropora corals may have an earlier onset and longer period of preparation for spawning than merulinid corals; and (2) merulinid corals may use moonlight signals near sunset, while Acropora corals may have a similar onset at approximately midnight. This is the first study to indicate the difference in circadian phase-dependent moonlight sensitivities between coral taxa, providing a basis for underlying coral spawning mechanisms for rhythmic studies.